ASSESSMENT OF LIVER FUNCTION TESTS IN THE SUBJECTS VISITING PMCH HOSPITAL (The Research of Medical Science Review, 2025)
OBJECTIVE: This study analyzes liver function and enzyme abnormalities, highlighting demographic, lifestyle, and comorbidity impacts for informed liver disease prevention.METHODOLOGY: This cross-sectional investigation was executed at PMC Hospital, Nawabshah, with the objective of evaluating hepatic function parameters and ascertaining the prevalence of hepatic function irregularities in the adult population. A total of 150 qualifying participants, aged between 18 and 65 years, were incorporated into the investigation. Clinical evaluations and laboratory analyses were conducted, encompassing the quantification of ALT, AST, ALP, GGT, bilirubin, and albumin concentrations. Data were subjected to analysis utilizing SPSS version 26.0, with statistical significance established at a p-value ≤ 0.05.RESULTS: The investigation encompassed a cohort of 150 participants, with a mean age of 53.23 ± 12.94 years, comprising 52% males and 48% females. The results of the liver function tests (LFT) indicated that the average ALT concentration was 34.11 ± 14.02 U/L and the average AST concentration was 30.70 ± 9.36 U/L among the subjects, with the average ALP level recorded at 100.61 ± 25.10 U/L, the average GGT level at 43.00 ± 18.77 U/L, the average total bilirubin level at 1.01 ± 0.30 mg/dL, and the average albumin level at 4.00 ± 0.35 g/dL.CONCLUSION: It is to be concluded that mild-to-moderate elevations of transaminases and cholestatic enzymes were observed in a substantial proportion. These abnormalities correlated with obesity, diabetes, and alcohol consumption. Our findings support routine LFT monitoring to detect subclinical liver injury early, inform hospital-specific reference intervals, and guide evidence-based screening. Longitudinal studies are needed to refine intervention thresholds and improve patient outcomes.